Identity Diffusion as the Organizing Principle of Borderline Personality Traits in Adolescents—A Non-clinical Study - Rivnyák, Adrienn; Pohárnok, Melinda; Péley, Bernadette; Láng, András (Frontiers in Psychiatry, 2021)
Growing evidence shows that diagnosing and treating borderline personality disorder (BPD) is of high relevance for affected youths. Although identity crisis is part of the normative developmental process, identity diffusion is a potential candidate for being an appropriate concept in further developing screening tools and interventions for BPD treatment in adolescence. We hypothesized that severity of borderline traits (as indicated by the strength of their associations with identity diffusion) would be negatively associated with non-clinical adolescents’ endorsement of borderline features’ presence. We also hypothesized that identity diffusion had a central role in the network of borderline personality traits and could be conceived of as a latent organizing principle of borderline personality disorder. In our study, 169 non-clinical adolescents (81 girls and 88 boys; Mage = 15.38; SDage = 1.52) filled out self-report measures of borderline personality features and identity diffusion. According to our results, having strong feelings and interpersonal sensitivity were the two most endorsed borderline personality features. Borderline personality features were positively correlated with identity diffusion. The more severe a borderline personality feature was, the less relevant it was for non-clinical adolescents. According to a network analysis, identity diffusion was the most central and least redundant element of the network of borderline personality traits. Results are discussed from a clinical point of view, further encouraging professionals to use identity diffusion screening tools to detect BPD in adolescence.